1991
DOI: 10.1111/j.1399-6576.1991.tb03238.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between morphine, meperidine and ketobemidone in continuous intravenous infusion for postoperative relief

Abstract: Morphine, meperidine and ketobemidone used in continuous i.v. infusion for postoperative pain relief were compared in a double-blind, controlled, prospective study in 81 consecutive consenting adult patients after open-heart surgery, with permission from the hospital ethics committee. During the first postoperative period, the infusion rates were fixed. Later on, when the infusion rate could be regulated according to individual patient needs, the variation in infusion rate was large, in accordance with earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The DDD is defined as the most common maintenance dose for the most common indication of any given drug and is determined by a World Health Organization expert group (WHO Collaborating Centre for Drug Statistics Methodology, 2010) The OMEQs of different opioids are more comparable in terms of equianalgesic effects as compared with the DDD. A literature search was conducted in Pubmed and Embase, as well as textbooks and websites, to create a table with equianalgesic ratios for all opioids and formulations used in this study (Ohqvist et al, 1991;Anderson et al, 2001;Souter and Fitzgibbon, 2004;Sittl et al, 2005;Divvela et al, 2006;Fredheim et al, 2006;Wall et al, 2006;Patanwala et al, 2007;Back, 2008;MacAuley, 2008;Norwegian Medicines Agency, 2011a,b). Using a previously described method (Jarlbaek et al, 2005;Svendsen et al, 2011), we calculated the OMEQ measured in milligram per prescription and then aggregated this to each individual.…”
Section: Oral Morphine Equivalentsmentioning
confidence: 99%
“…The DDD is defined as the most common maintenance dose for the most common indication of any given drug and is determined by a World Health Organization expert group (WHO Collaborating Centre for Drug Statistics Methodology, 2010) The OMEQs of different opioids are more comparable in terms of equianalgesic effects as compared with the DDD. A literature search was conducted in Pubmed and Embase, as well as textbooks and websites, to create a table with equianalgesic ratios for all opioids and formulations used in this study (Ohqvist et al, 1991;Anderson et al, 2001;Souter and Fitzgibbon, 2004;Sittl et al, 2005;Divvela et al, 2006;Fredheim et al, 2006;Wall et al, 2006;Patanwala et al, 2007;Back, 2008;MacAuley, 2008;Norwegian Medicines Agency, 2011a,b). Using a previously described method (Jarlbaek et al, 2005;Svendsen et al, 2011), we calculated the OMEQ measured in milligram per prescription and then aggregated this to each individual.…”
Section: Oral Morphine Equivalentsmentioning
confidence: 99%
“…Where authors reported opioid use, we converted to oral morphine equivalents to facilitate comparison. 27,28 The variables worst pain, pain with movement, and worst pain with movement were pooled for analysis as a single outcome measure, as we felt these were all indicative of the patients' maximum pain. Methodologic quality of each study was scored independently by 2 of the authors (M.F.A. and A.E.B.)…”
Section: Data Extraction and Quality Analysismentioning
confidence: 99%
“…Analgesic efficacy and medical use: Ketobemidone is a potent analgesic and is used for the treatment of moderate to severe pain (Ohqvist et al, 1991).…”
Section: Synthesis'mentioning
confidence: 99%